Fire and flood occurrence in the habitats of the endangered butterfly Coenonympha oedippus in Slovenia - Zupan, Sara; Bužan, Elena; Čelik, Tatjana; Kovačič, Gregor; Jugovic, Jure; Martina (Acta geographica Slovenica, 2023)
In Slovenia the False ringlet Coenonympha oedippus uniquely occurs both on wet (Ljubljana Marsh and surroundings) and dry grasslands (Slovenian Istria, Karst, Gorica Hills). Natural hazards that threaten its habitats include fires and floods; the frequency of their occurrence in the former and existing habitats of C. oedippus was determined using the χ2-test. We showed that habitats on wet grasslands are less threatened by fire than those on dry grasslands. Among the latter, habitats in the Karst and Slovenian Istria are the most threatened. Habitats of C. oedippus are threatened by flooding only in Slovenian Istria and Ljubljana Marsh. Considering the extent of fire and flood risk and fragmentation of C. oedippus habitats in Slovenia, we assume that such natural hazards may lead to local extinction of the species.